Crystal field excitations on NdFe3(BO3)4 investigated by inelastic neutron scattering. (September 2016) - Hayashida, S.; Soda, M.; Itoh, S.; Yokoo, T.; Ohgushi, K.; Kawana, D.; Masuda, T.
Abstract: We performed inelastic neutron scattering experiments on a multiferroic material NdFe3 (BO3 )4 to explore the crystal field excitations, where the magnetic anisotropy of the Nd 3+ crystal field was responsible for the multiferroicity. Flat modes were observed at 8.5 meV and 17.4 meV in the neutron spectrum. The analysis revealed that these excitations were the transitions from the ground state to the first and second excited states of the Nd 3+ crystal field.